2014
DOI: 10.1002/ijch.201400043
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Solid‐State White Light‐Emitting Electrochemical Cells

Abstract: Compared to organic light‐emitting diodes, solid‐state light‐emitting electrochemical cells (LECs) exhibit advantages of simple device structures, low operation voltages, and compatibility with air‐stable metal electrodes. Since the first demonstration of white LECs in 1997, the cells have been studied extensively, due to their potential applications in solid‐state lighting. This article reviews the development of white LECs based on conjugated polymers and cationic transition metal complexes. Important achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 72 publications
0
42
0
Order By: Relevance
“…However, although the electrical tolerance of LECs to the active-layer thickness has been well established through, e.g., the successful operation of mm-wide planar devices at a few volts drive voltage 22 , 23 , the corresponding optical dependence is less studied and comparatively poorly understood 24 , 25 . It has been demonstrated that losses due to doping-induced self-absorption become increasingly prominent as the active-layer thickness increases 26 , 27 , while an enhanced emission color or efficiency has been attributed to scattering 28 , 29 , microcavity 30 , 31 , and waveguide-coupling effects 32 .…”
Section: Introductionmentioning
confidence: 99%
“…However, although the electrical tolerance of LECs to the active-layer thickness has been well established through, e.g., the successful operation of mm-wide planar devices at a few volts drive voltage 22 , 23 , the corresponding optical dependence is less studied and comparatively poorly understood 24 , 25 . It has been demonstrated that losses due to doping-induced self-absorption become increasingly prominent as the active-layer thickness increases 26 , 27 , while an enhanced emission color or efficiency has been attributed to scattering 28 , 29 , microcavity 30 , 31 , and waveguide-coupling effects 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Light emission from electronic devices can be achieved using a number of physical processes, resulting in a variety of device architectures, all of which have in common that they require a complex stack of various functional materials, some of which need to be deposited as a continuous homogeneous film, whereas others must be structured. The working principles of light emitting electrochemical cells (LECs), electroluminescent devices using alternating voltage (AC‐EL), and organic light emitting diodes (OLEDs), have been described in detail and therefore will not be explained here again. All these devices need some type of transparent electrode structure and highly conductive wiring, which has been discussed already in the two sections above.…”
Section: Light Emitting Devicesmentioning
confidence: 99%
“…Before turning our attention to the more specific recent progress in the LEC field, we wish to acknowledge and direct the reader's attention to previous important summaries and reviews on LEC research, as provided by Refs. [22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%